Comparative long-term effectiveness and safety of primary bariatric surgeries in treating type 2 diabetes mellitus in adults: a protocol for systematic review and network meta-analysis of randomised controlled trials. Issue 4 (4th April 2019) - Ding, Li; Zhuo, Chuanjun; Fan, Yuxin; Zhang, Yalan; Li, Hui; Qi, Dongwang; Tang, Shaofang; Cui, Jingqiu; He, Qing; Liu, Ming
Abstract : Introduction: Bariatric surgeries are effective in treating obesity related comorbidities, including type 2 diabetes mellitus. More robust evidence is needed to facilitate choice of procedure. In this systemic review, we aim to investigate the comparative long-term effectiveness in inducing remission of type 2 diabetes, halting diabetic complications, reducing mortality and the safety of conventional and emerging bariatric surgeries. Methods and analysis: Databases including Cochrane Central Register, EMBASE, MEDLINE and clinical trial registries will be searched for randomised controlled trials with at least 3 years of follow-up, including direct and/or indirect evidence regarding primary bariatric surgeries in overweight or obese adults with type 2 diabetes mellitus, from inception of each database to 2019, with no language or publication type limits imposed. Dual selection of studies, data extraction and risk of bias assessments will be performed. Primary outcomes include full diabetes remission, composite outcome of full or partial diabetes remission and adverse event profiles. Secondary outcomes include anthropometric measurements, cardiovascular risk factor burden, medication burden, diabetic complications and all-cause mortality. Given sufficient homogeneity, network meta-analyses will be performed in a random-effects model based on the Bayesian framework, while assessing for consistency between direct and indirect estimates. Heterogeneities of studies will be explored through meta-regression analysis, and robustness of findings will be checked by sensitivity analysis, and an alternative method under a frequentist framework. All statistical analysis and graphical presentations will be conducted by R software V.3.3.3 (The R Project for Statistical Computing). The overall quality of the evidence will be assessed using the Grading of Recommendations, Assessment, Development and Evaluation criteria for each outcome. Ethics and dissemination: Ethics approval is not required as individual patient data will not be included. This review will be subject for publication in a peer reviewed journal. PROSPERO registration number: CRD42018110775.